Defining a need for rapid response and practical guidance for recurrent and metastatic squamous cell carcinoma of the head and neck (R/M SCCHN) management in France: A Delphi consensus - Florian Clatot; Caroline Even; Amaury Daste; Christian Borel; Jérôme Fayette; Myriam Chebbah; Solenn Le Clanche; Esma Saada (PLoS ONE, 2025)
Background Recurrent and metastatic squamous cell carcinoma of the head and neck (R/M SCCHN) presents substantial treatment challenges due to its aggressive and heterogeneous nature. While evidence-based guidelines provide useful recommendations, they may not offer sufficient support for real-time clinical decision-making. Objective This Delphi consensus aimed to establish expert agreement on clinical parameters guiding first- and second-line treatment decisions and the management of specific clinical scenarios in R/M SCCHN in France. Methods A two-round Delphi consensus was conducted between December 2023 and June 2024. A scientific committee of six national experts developed consensus statements based on a literature review and supervised the process. An expert panel of 25 oncologists from across France participated in both rounds. Results All respondents agreed that the need for a rapid therapeutic response and the presence of comorbidities were critical factors influencing first-line treatment choice. Seven major indicators of rapid response were identified: rapidly progressive relapse, partial airway obstruction, respiratory compromise, tumour-related bleeding, uncontrolled symptoms, carotid axis lesions, and pain resistant to third-step analgesics. For patients requiring rapid response, 76% supported using cetuximab with chemotherapy as a first-line option in cases with a combined positive score (CPS) between 1 and 19. Furthermore, 84% recommended immunotherapy (alone or combined with chemotherapy) as first-line treatment for CPS ≥ 20 tumours, while 41% would consider it for CPS 1–19 cases. A strong consensus (80%) held that first-line treatment should not restrict second-line options. Notably, 100% of respondents agreed that all patients should receive immunotherapy, cetuximab, taxanes, and platinum salts within the first two treatment lines. Conclusions This Delphi consensus offers valuable, expert-based perspectives on the management of R/M SCCHN in France. It highlights a progressive shift from standardized European guideline frameworks toward a more personalized approach that accounts for individual patient profiles and tumour characteristics. The insights generated provide practical guidance for clinical decision-making and lay the groundwork for future research and optimisation of treatment strategies in real-world settings.